2006
DOI: 10.3102/01623737028003215
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Policies Related to Developmental Education: An Evaluation Using the Regression-Discontinuity Design

Abstract: Utilizing the regression-discontinuity research design, this article explores the effectiveness of a developmental English program in a large, multicampus community college. Routinely collected data were extracted from existing records of a cohort of first-time college students followed for approximately 6 years (N = 1,473). Results are consistent with a conclusion that students’ participation in the program increases English academic achievement to levels similar to those of students not needing developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 20 publications
3
62
1
Order By: Relevance
“…Lesik (2006) studied three cohorts of first-time, full-time students at a large state university and found that developmental education improves the chances of completing a first-level college math course on the first try. Moss and Yeaton (2006) studied students at a large community college and concluded that students who took developmental English do as well in subsequent college courses as students who scored above the developmental cutoff score.…”
Section: T Otal College-level Credits Earnedmentioning
confidence: 99%
“…Lesik (2006) studied three cohorts of first-time, full-time students at a large state university and found that developmental education improves the chances of completing a first-level college math course on the first try. Moss and Yeaton (2006) studied students at a large community college and concluded that students who took developmental English do as well in subsequent college courses as students who scored above the developmental cutoff score.…”
Section: T Otal College-level Credits Earnedmentioning
confidence: 99%
“…Many colleges provide higher education opportunities through open access to students who are underprepared for college-level courses (Moss & Yeaton, 2006). However, simply providing opportunity may not be sufficient to deal with academically underprepared students, who may require further development and training to integrate them into higher education better (Boylan, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One outcome of this Act was the initiation of open-access policies that encouraged more students to attend college regardless of their academic preparedness by offering incentives of interest-free loans, part-time jobs, and need-based scholarships (Bankston, 2011;Mulvey, 2008;Salas, Portes, D'Amico, & Rios-Aguilar, 2011). While open access policies were meant to increase accessibility to higher education, an unintended result has been a substantially higher increase in academically underprepared college students (Moss & Yeaton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moss and Yeaton define remediation as a practice that is guided by learning theory and includes non-credit courses that address fundamental skills that students lack that is determined by college placement examinations. 25 Alternatively, per Moss and Yeaton, developmental education considers the life experiences of the students in addition to their entering skill level. Developmental education emphasizes the need for students to become independent and have self-regulation in their learning, rather than focusing on a deficit perspective of education, as is the case with remediation.…”
Section: Stage 1 Resultsmentioning
confidence: 99%